Clinical Course of Untreated and Treated Chronic Hepatitis B in Pregnant Patients: A Prospective Study - Nadir, Yasemin; Batirel, Ayse; Karsidag, Ayse Yasemin; Narter, Fatma Kaya; Nadir, Ahmet (Gynecology Obstetrics & Reproductive Medicine, 2021)
OBJECTIVE: Implementation of strategies to prevent vertical transmission is highly important steps in reducing the global burden of chronic hepatitis B. We conducted this prospective study to observe the clinical course and outcomes of untreated and treated HBV in pregnant. STUDY DESIGN: HBsAg-positive pregnants were prospectively enrolled from 2013 to 2016 and antiviral therapy was administered to eligible patients. Pregnancy and neonatal outcomes were determined in the treated (n=29) and untreated group (n=136). Active-passive immunoprophylaxis was administered to infants and they were tested for HBsAg. RESULTS: The risk factors for transmission (HBeAg positivity, history of previously-born HBsAg-positive child) were significantly higher in the treated group. All participants under treatment had sufficient viral suppression. Half of the pregnant women for whom the treatment was withheld at the postpartum period, experienced increased viral load. The treated group had significantly higher pre- and postpartum alanine aminotransferase levels more than the untreated group, although there were no significant differences in other biochemical parameters. There were no significant differences regarding fetal outcomes between the two groups. All infants were HBsAg-negative at seven months postpartum. CONCLUSION: While the untreated group included inactive carriers, there were more patients at risk for transmission of HBV to their offsprings in the treated group. Half of the pregnant women for whom the treatment was withheld at the postpartum period, experienced increased viral load. Antiviral therapy did not adversely affect the outcomes of infants. As a result, we successfully prevented perinatal HBV transmission by close monitoring of participant pregnant women and starting antiviral therapy when needed.